If it's not what You are looking for type in the equation solver your own equation and let us solve it.
X2-2X-35=0
We add all the numbers together, and all the variables
X^2-2X-35=0
a = 1; b = -2; c = -35;
Δ = b2-4ac
Δ = -22-4·1·(-35)
Δ = 144
The delta value is higher than zero, so the equation has two solutions
We use following formulas to calculate our solutions:$X_{1}=\frac{-b-\sqrt{\Delta}}{2a}$$X_{2}=\frac{-b+\sqrt{\Delta}}{2a}$$\sqrt{\Delta}=\sqrt{144}=12$$X_{1}=\frac{-b-\sqrt{\Delta}}{2a}=\frac{-(-2)-12}{2*1}=\frac{-10}{2} =-5 $$X_{2}=\frac{-b+\sqrt{\Delta}}{2a}=\frac{-(-2)+12}{2*1}=\frac{14}{2} =7 $
| 15/27=n/9 | | -6|x|=-36 | | 5n^2(n^2-2)=80-19n^2 | | x-x/1/6=25 | | 35+3x–11=23 | | 2/11w+9/w=1 | | 20+x+5=90 | | 0.5+4=2(b+2 | | x2−12x+36=0 | | (35+x)/12=10 | | (-2x-3)(-9x+7)=0 | | 5p+17=2 | | 6(5m-3)=1/3(24m=12) | | 8y=5 | | 7x=3.5x+80 | | 52-(x/7)=15 | | 7(3-(5+2x)-2x)=-16+2(1-8x) | | 6(3x-4)=46 | | ((2x^2)/x+1)+1=(2/(x+1)) | | 7(x+4)+3(x+4)=5x-5 | | -2t^2+15t-50=0 | | y-10.24=5.23 | | |2x-6|=22 | | x/3-3/4=(2x+9/12) | | 5x=4x+6+16/x | | x+7=2x+5−4x | | 3/z=15/7 | | 2x^2/x+1+1=2/x+1 | | 8(z-2)=9z-18 | | 2(z+4)=4z+2 | | 26−4s=9s26−4s=9s | | Y=40000-0.2x |